On the Touch-Event: Theopolitical Encounters. - Napolitano, Valentina (Social Analysis, 2020)
This article addresses the 'touch-event' as a mediated affective encounter that pivots around a tension between intimacy and distance, seduction and sovereignty, investment and withdrawal. Through a rereading of the Pauline event of conversion to Christianity, it argues that an analysis of the evolving significance of touch-events for Catholic liturgy and a religious congregation shows the theopolitical as always already constituted within an economy of enfleshed virtues. Focusing on contemporary examples of touch-events from the life of Francis, the first pope from the Americas, as well as from fieldwork among a group of female Latin American Catholic migrants in Rome, I argue for a closer examination of touch-events in order to grasp some of their theopolitical, radical, emancipatory, and, in some contexts, subjugating effects.